2021
DOI: 10.1002/jbio.202100107
|View full text |Cite
|
Sign up to set email alerts
|

Raman confocal microscopy and biophysics multiparametric characterization of the skin barrier evolution with age

Abstract: Skin aging is a multifactorial phenomenon that involves alterations at the molecular, cellular and tissue levels. Our aim was to carry out a multiparametric biophysical and Raman characterization of skin barrier between individuals of different age groups (<24 and >70 years old). Our results showed a significant decrease of lipids to proteins ratio overall the thickness of the stratum corneum and higher lateral packing in the outer part of the SC for elderly. This can explain the decrease in trans epidermal wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 55 publications
0
11
0
1
Order By: Relevance
“…In older humans, keratin is in more unfolded state compared to younger humans [39], which was recently confirmed by Rigal et al [60]. Porcine skin, which is widely used as an ex vivo model of human skin in dermatological research, has more exposed secondary structure of keratin at ≈10–90% SC depth ( p < 0.01), and a more folded tertiary structure of keratin at ≈30–100% SC depth ( p < 0.05) in comparison with human SC in vivo, which determines binding of water inside the corneocytes [62].…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…In older humans, keratin is in more unfolded state compared to younger humans [39], which was recently confirmed by Rigal et al [60]. Porcine skin, which is widely used as an ex vivo model of human skin in dermatological research, has more exposed secondary structure of keratin at ≈10–90% SC depth ( p < 0.01), and a more folded tertiary structure of keratin at ≈30–100% SC depth ( p < 0.05) in comparison with human SC in vivo, which determines binding of water inside the corneocytes [62].…”
Section: Resultsmentioning
confidence: 70%
“…and 50 y.o. age-groups) [39], which was recently confirmed by Rigal et al [60]. The lipid organization is changed toward decreasing of skin barrier function in the xerosis and atopic skin in vivo [32, 61].…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…With age, the skin naturally has decreased lamellar body secretions, depletion of lipids, slower barrier repair, and increased TEWL [ 53 , 54 ]. Though the global stratum corneum water content decreases with age [ 55 ], the surface stratum corneum water content has been shown to be similar in both young and aged skin [ 56 ].…”
Section: Pathophysiology Associated With Diabetic Wound Healingmentioning
confidence: 99%
“…A recent study further analyzed water content in different stratum corneum layers, revealing similar amounts at the surface. At the same time, the authors found higher water content in deep parts of the stratum corneum and viable epidermis in aged skin [ 3 ]. This is explained by an age-dependent change in the amount of bound and unbound water.…”
mentioning
confidence: 99%